PRINSIP KEHATI-HATIAN PADA AKAD QARDH DALAM PERBANKAN SYARIAH DI INDONESIA - Herjanriasto Bekti Nugroho (Al-Amwal : Journal of Islamic Economic Law, 2020)
This study aims to determine the application of the precautionary principle in the implementation of the Qardh Agreement in Islamic Banking and the comparison of the implementation of lending and borrowing between Islamic banks and conventional banks. The results of the study indicate that in Sharia Banking activities must apply the precautionary principle in accordance with the provisions of Article 35 paragraph (1) of Law Number 21 Year 2008 concerning Sharia Banking by applying the 5C principle consisting of character, capacity, capital, condition of economy , and collateral included in the implementation of the Qardh Agreement. In Islamic banking, customers who want to lend money to banks for certain purposes can use either the qardh or qardhul hasan contracts. The qardh and qardhul hasan contracts referred to are certainly different from credit agreements with conventional banks, because customers who enter into credit agreements with conventional banks must return the money to the bank and interest.